UJI ANTAGONIS BAKTERI ENDOFIT TERHADAP Colletotrichum scovillei PENYEBAB PENYAKIT ANTRAKSONA PADA CABAI BESAR (Capsicum annuum L.) - Wibawa, I Gede Karta Satria; Suprapta, Dewa Ngurah; Khalimi, Khamdan (Journal of Agricultural Science and Biotechnology; Vol 8 No 1 (2019), 2019)
Colletotrichum scovillei is a newly discovered species causing anthracnose disease on chilli pepper (Capsicum annuum L.) in Bali. With the increasing reports of Colletotricum spp. resistance against chemical fungicide, biological control is taken as the alternatives to control this disease. In this study a total of 69 endophytic bacteria isolates was recovered from different solanaceae plants samples collected from nine regions of Bali and screened for the antagonism againstC. scovillei. From the potential 15 candidates of isolates with inhibition activity above 90%, hypersensitivity test were taken on tobacco leaf, and isolate CBCKB1 was chosen for further test. The CBCKB1 isolate was identified as Bacillus amyloliquefaciens based on molecular identification. Detached fruit bioassay proved that isolate CBCKB1 formula was effective in reducing the disease percentage and disease severity of anthracnose disease on chilli pepper.